2019
DOI: 10.1042/bsr20181896
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor gene polymorphisms are associated with silicosis: a systemic review and meta-analysis

Abstract: Studies investigating association between tumor necrosis factor (TNF) gene polymorphisms and silicosis susceptibility report conflicting results. The aim of this meta-analysis was to assess association between TNF gene polymorphisms and silicosis susceptibility. A systematic literature search was conducted to find relevant studies. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the strength of association. Finally, a total of 12 articles, involving 1990 silicosis patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…4,9,22,23 Of the six studies analyzed, five evaluated TNF-α concentrations and one investigated the presence of the -308G/A polymorphism, which is a G to A mutation at the -308 position in the promoter region, and is associated with higher levels of TNFα. 13 Despite the fact that these studies are difficult to compare because different fluids were used to measure the concentration of this interleukin, all lead us to reflect on the possibility of developing a more targeted treatment. Two articles 16,18 found a significant difference in TNF-α levels of patients compared to (20), indicating that this interleukin level is higher in patients with greater disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,9,22,23 Of the six studies analyzed, five evaluated TNF-α concentrations and one investigated the presence of the -308G/A polymorphism, which is a G to A mutation at the -308 position in the promoter region, and is associated with higher levels of TNFα. 13 Despite the fact that these studies are difficult to compare because different fluids were used to measure the concentration of this interleukin, all lead us to reflect on the possibility of developing a more targeted treatment. Two articles 16,18 found a significant difference in TNF-α levels of patients compared to (20), indicating that this interleukin level is higher in patients with greater disability.…”
Section: Discussionmentioning
confidence: 99%
“…12 The single nucleotide polymorphism (SNP) -308G/A TNF-α rs1800629 is characterized by the replacement of guanine (G) with adenine (A) in the promoter region of the gene, which leads to a greater production of this interleukin. 13 Only a few studies have evaluated the presence of interleukins and genetic polymorphisms in TMD patients, but they have provided important results regarding the role of tumor necrosis factor. This has pointed to the possibility of the inclusion of this immune-inflammatory marker of immunity in the evaluation of Dental Press J Orthod.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that TNF-α manufacture is managed at the transcriptional level 9 , and a G-to-A mutation in the −238, −308 promoter area is linked by an raise in TNF-α manufacture 10 . Furthermore, in spite of the fact that TNF-α promoter have four particular point mutations of G to A are distinguished at the -163, -238, -308, and -376 locales, respectively 11,12 , which may influence TNF -α expression 13 , investigations have shown the SNPs at -238 and -308 are associated with the happened and development of silicosis 8,10,14 . thus, we suppose that polymorphisms in the TNF-α (-308) promoter region is associated with respiratory inflammation risk in concrete laborers.…”
Section: Introductionmentioning
confidence: 99%
“…Yucesoy et al (2001), based on the results obtained from a case-control study involving male Caucasian underground miners (325 cases and 164 controls), found a strong association between silicosis incidence and polymorphisms of the TNF-a gene. Similarly, based on the results of a meta-analysis involving 1990 silicosis and 1898 healthy controls, Zhang et al (2019) concluded that TNF-a polymorphisms are associated with susceptibility to silicosis. Nevertheless, contrary to the findings of these reports, there are studies that failed to demonstrate an association between silicosis and TNF-a polymorphisms (Qu et al, 2007;Wu et al, 2008).…”
mentioning
confidence: 99%